Development of multi-level standards of care recommendations for sickle cell disease: Experience from SickleInAfrica - Paintsil, Vivian; Ally, Mwashungi; Isa, Hezekiah; Anie, Kofi A.; Mgaya, Josephine; Nkanyemka, Malula; Nembaware, Victoria; Oppong-Mensah, Yaa Gyamfua; Ndobho, Flora; Chirande, Lulu; Makubi, Abel; Nnodu, Obiageli; et al. (Frontiers in Genetics, 2023)
Introduction: Sickle Cell Disease (SCD) causes significant morbidity and mortality particularly in sub-Saharan Africa (SSA) where it contributes to early childhood deaths. There is need to standardize treatment guidelines to help improve overall SCD patient health outcomes. We set out to review existing guidelines on SCD and to set minimum standards for management of SCD for the different referral levels of healthcare. Methods: A standards of care working group (SoC-WG) was established to develop the SoC recommendations. About 15 available SCD management guidelines and protocols were reviewed and themes extracted from them. The first draft was on chosen themes with 64 major headings and subtopics. Using a summarised WHO levels of referral document, we were able to get six different referral levels of healthcare. The highest referral level was the tertiary facilities whilst the lowest level was the home setting. Recommendations for SCD management for the regional, district, sub-districts, health posts and CHPs compounds were also drafted. Results: The results from this review yielded a guidelines document which had recommendations for management of SCD on 64 topics and subtopic for all the six (6) different referral levels. Discussions: Every child with SCD need to receive comprehensive care that is coordinated at each level. This recommendation is unique in terms of the availability of recommendations for different levels of care as compared to the traditional guidelines which is more focused at the tertiary levels. Patients can access care at any of the other lower referral hospitals and be managed with recommendations that are in keeping with institutional resources at that level. When such patients need care that requires expertise that is not available at that level, the recommendations will be to refer to the appropriate referral level where those expertise are available. This encourages patients to have good clinical care nearer their homes but also having access to specialist screening modalities and expertise at the tertiary hospitals if need be. With this, patient are not limited to a specific referral level when interventions cannot be instituted for them. Conclusion: This SoC recommendations document is a useful material that can be used for consistent standards of treatment in SSA.